Körsång och lust:: En undersökning av körsång som sinnlig aktivitet och erfarenhet - Elam, Katarina (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2009)
This article investigates choir singing as an embodied, sensuous experience. I have chosen a bundle of concepts which I think are foundational for singing, especially singing together in a choir. The concepts in question are embodiment, pleasure, and community, and by narrowing down the meaning of these concepts in this particular context, I try to make the phenomenon of choir singing appear. Choral singing is an aesthetic experience which embraces feelings of presence and engagement as an embodied subject; creating and reception; pleasure and happiness; being part of and a whole simultaneous, together. Thus, it is not possible to clearly demarcate the object for the investigation but in the frame of "choral singing and pleasure" I will illuminate the aspects that I find most relevant. The whole discussion ends up in some reflections concerning similarities between aesthetic and religious experience which would be interesting to deepen in the future.